Dynamics in Implementing the Concept of Anti-Bullying Education Based on Prophet’s Sunnah - Sartini, Titi; Ismail, M. Syukri (UIN Sjech M. Djamil Djambek Bukittinggi, 2024)
The background of this paper is the prevalence of bullying behavior in society. Bullying behavior almost colors all aspects of life, especially in the political year. So that the success of our education is questioned. History has proven that the jahiliyyah tradition can turn into a prophetic tradition. The Prophet Muhammad was successful in instilling anti-bullying values. The approach used is qualitative, using the Library Study method (library research), and research relies on library data. This study found that there were 3 main methods of anti-bullying education carried out by the Prophet Muhammad, namely: first, the Prophet became a model, uswah hasanah, a role model in educating friends. Second, the Prophet Muhammad told the companions to carry out the teachings of Islam. Third, the Prophet Muhammad prohibited or condemned bullying.